INFLUENCE OF THERAPEUTIC AND PROPHYLACTIC COMPLEX ON BIOCHEMICAL PARAMETERS OF RAT MUCOUS MEMBRANE OF GUMS UNDER MODELING OF EXPERIMENTAL CARIES - Sukhomeylo, D.O.; Reyzvikh, O.E.; Shnaider, S.A.; Khrystova М.Т.; Kalynchuk, S.V.; Maslov, O.V. (World of Medicine and Biology, 2024)
The purpose of this study was to assess the effect of the proposed therapeutic and prophylactic complex on the biochemical parameters of the oral mucosa of rats under conditions of modeling experimental caries against the background of alimentary deficiency of vitamin D. Experimental studies were conducted on 42 one-month-old Wistar rats of both sexes, which were divided into 3 groups. Gingival homogenates were prepared and the level of biochemical markers of systemic inflammation was determined: elastase activity and malondialdehyde content, as well as urease activity, catalase activity and acid phosphatase activity. The therapeutic and prophylactic use of the proposed complex in rats helps to inhibit the detected disorders under conditions of experimental caries against the background of nutritional deficiency of vitamin D, normalizing the studied parameters to the level of intact animals, which indicates the expressed antioxidant, anti-inflammatory and antimicrobial properties of the complex.